Variations of TEC Over Iberian Peninsula in 2015 Due to Geomagnetic Storms and Solar Flares - A. L. Morozova; T. V. Barlyaeva; T. Barata (Space Weather)
Abstract The total electron content (TEC) over the Iberian Peninsula was studied using data from two locations obtained both by Global Navigation Satellite System receivers and an ionosonde. The principal component analysis applied to the TEC data allowed us to extract two main modes. Each mode is characterized by a daily TEC variation of a certain type (principal component [PC]) and its amplitude for each of the studied days (given by the empirical orthogonal functions [EOFs]). The variations of these modes as well as the original TEC data were studied in relation to four strongest geomagnetic storms of 2015 and three geomagnetic disturbances of lower amplitude observed during the same months. EOFs were found to correlate well with space weather parameters characterizing solar UV and XR fluxes, number of the solar flares, parameters of the solar wind, and geomagnetic indices. Multiple regression models were constructed to fit EOFs using combinations of the space weather parameters with a lag from 0 to 2 days. Combining the regression models of EOFs with the corresponding PCs, we reconstructed TEC variations as a function of space weather parameters observed in previous days. The possibility to use such reconstructions for the TEC forecasting was also studied.